Factors influencing rate of gain, amount of feed consumed and carcass grade - Bell, F.W.; Mackintosh, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
This is the second trial to study the effect of differences which can be observed in feed calves classified as good to choice. The two lots in this trial were sorted from the 100 range-bred heifer calves purchased last November for feeding experiments at this station. This was a very uniform shipment of calves with no plain ones in the group. Sorting for the two lots of calves was made on apparent differences in capacity for feed, chest room, muscling, bone, and general appearance. The individual calves also were graded by using a standard feeder chart.
Keywords: Beef; Rate of gain; Feed consumption; Carcass grade